Culture and Spirituality-Based Tourism Job Training Institution at The Hotel International School Bali - I Putu Agus Bramadi Arinatha; Ketut Sumadi; I Made Arsa Wiguna (Jurnal Ilmiah Hospitality Management, 2026)
Tourism education and job training have a strategic role in shaping the quality of human resources. This research aims to analyze and build the concept of a culture and spirituality-based tourism job training institution (LPK) developed at the Bali International School Hotel. This study uses a descriptive qualitative approach with purposive sampling techniques. The research informants include LPK managers, instructors, training participants, and tourism industry stakeholders. Data collection was carried out through in-depth interviews, participatory observations, and documentation studies. The results of the study show that the integration of Balinese cultural values and Hindu spirituality based on the Tri Hita Karana philosophy is carried out systematically in the curriculum, learning process, and job training practice. This training model is able to bridge global tourism competency standards with local Balinese wisdom, resulting in graduates who are professional, characterful, and adaptive to the dynamics of the international tourism industry.